Carcass Quality Percentage and Carcass Components of Stunted Broiler Chickens Supplemented with Moringa (Moringa Oleifera) Leaf Meal in The Diet - Sugiarto, Sugiarto; Marfuah, Nuun; Gunawan, Aynan Hismafanti (Universitas Sebelas Maret, 2026)
Objective: This study aimed to evaluate the effect of different inclusion levels of Moringa (Moringa oleifera) leaf meal on carcass percentage and carcass components of broiler chickens affected by stunting syndrome.Methods: Describe briefly the main materials and methods or treatments applied including data analysis. A Completely Randomized Design (CRD) with five dietary treatments was used: P0 = 0% (control), P1 = 4%, P2 = 6%, P3 = 8%, and P4 = 10% Moringa leaf meal. Each treatment was replicated five times. Parameters measured included final body weight, carcass percentage, and carcass components (breast, thigh, drumstick, back, and wing). Data were analyzed using ANOVA, and significant means were compared with Duncan’s Multiple Range Test.Results: The inclusion of Moringa leaf meal had a highly significant effect (P<0.01) on final body weight, breast, and thigh components, and a significant effect (P<0.05) on back percentage. However, it had no significant effect (P>0.05) on overall carcass percentage, drumstick, and wing components. Stunting syndrome reduced growth performance due to abnormal physical conditions and limited nutrient utilization.Conclusions: Supplementation of Moringa leaf meal, which contains high levels of protein, vitamins, minerals, and bioactive compounds with antibacterial and antioxidant activities, has the potential to enhance nutrient absorption, improve muscle development, and contribute to better carcass yield and quality in broiler chickens with stunting syndrome.Keywords: Broiler chicken; Carcass components; Carcass percentage; Moringa leaf meal; Stunting syndrome